PENGUJIAN AKTIVITAS ANALGETIK INFUSA HERBA KROKOT (Portulaca oleracea L.) PADA MENCIT PUTIH (Mus musculus) MENGGUNAKAN METODE HOT PLATE - Azizah, Rizqi Nur; Putra, Bayu; Alda, Alda (As-Syifaa Jurnal Farmasi, 2024)
Analgesics are substances that can reduce pain. However, long-term use may trigger side effects. This study aimed to evaluate the analgesic effect of purslane herb infusion (Portulaca oleracea L.) using a pain stimulation method and determine its effective concentration as an analgesic in white mice (Mus musculus). The research was conducted experimentally using male white mice divided into five treatment groups: Group I received Na-CMC as a negative control, Group II received paracetamol suspension as a positive control, and Groups III, IV, and V received the infusion at concentrations of 10%, 20%, and 30%, respectively. Test animals were placed on a hot plate at a temperature of 55°C, and the pain response time to heat stimulation was observed every 30 minutes for 3 hours. The data were statistically analyzed using one-way ANOVA followed by Bonferroni post hoc tests. The positive control group showed no significant differences compared to the groups receiving 10%, 20%, and 30% infusion concentrations. The study concluded that the purslane herb infusion has an analgesic effect in white mice, with an effective concentration of 30%.